2016
DOI: 10.1371/journal.pone.0143047
|View full text |Cite
|
Sign up to set email alerts
|

Dogs Evaluate Threatening Facial Expressions by Their Biological Validity – Evidence from Gazing Patterns

Abstract: Appropriate response to companions’ emotional signals is important for all social creatures. The emotional expressions of humans and non-human animals have analogies in their form and function, suggesting shared evolutionary roots, but very little is known about how animals other than primates view and process facial expressions. In primates, threat-related facial expressions evoke exceptional viewing patterns compared with neutral or positive stimuli. Here, we explore if domestic dogs (Canis familiaris) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 65 publications
2
93
3
Order By: Relevance
“…Although we cannot determine the degree of attention that dogs paid to our stimuli, this interpretation is compatible with the fact that happy faces are salient for dogs. Several behavioral studies in dogs have not found differences between happy and neutral human faces 5,6,28,33 , yet we found differences in brain activity related to these two types of stimuli. Our results suggest that the specific brain activity to happy human faces reflects that these stimuli are important for dogs.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although we cannot determine the degree of attention that dogs paid to our stimuli, this interpretation is compatible with the fact that happy faces are salient for dogs. Several behavioral studies in dogs have not found differences between happy and neutral human faces 5,6,28,33 , yet we found differences in brain activity related to these two types of stimuli. Our results suggest that the specific brain activity to happy human faces reflects that these stimuli are important for dogs.…”
Section: Discussioncontrasting
confidence: 78%
“…An interesting study showed that once dogs learn from images of their owners' faces to discriminate a smiling face from a neutral face, they can generalize their learning to other humans of the same gender as their owners 2 . An eye-tracking study 6 found that dogs use a conjunction of information from eyes, midface, and mouth (i.e., inner face) to process faces in general; however, when looking at a pleasant human face, dogs spend significantly more time looking at the eyes in comparison to the mouth. The same authors also found different gazing patterns when dogs looked at threating and pleasant human faces, but not between pleasant and neutral faces.…”
Section: Introductionmentioning
confidence: 99%
“…a toaster, a coffee maker, a wall clock, a backpack) from the BOSS database [63]. The face stimuli were characterized with facial action coding system (FACS, [64]) and dog-FACS [8], and they were first used in a study examining dogs’ gazing patterns; for more details of the human and dog faces, see [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, dogs have many of the same muscles that produce facial expressions in humans [8], and their facial expressions are connected to the affective situation [9]. Dogs can differentiate emotions displayed by either human or dog facial expressions [1012], and they also show rapid facial mimicry in response to a conspecific expression during play [13]. Facial expressions thus provide important information of conspecific emotions also for dogs; they reflect at least some of their emotional states by the face and react to others’ expressions accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, the same held true for the patient’s dog in the presented case. Findings of a study with voluntary eye gaze of domestic dogs suggest that dogs evaluate social threat rapidly and that they do not base their perception of facial expressions on the viewing of a single structure, but on the interpretation of a constellation of areas comprising eyes, mid-face and mouth 13. Huber et al 14 showed that dogs expressed more behavioural indicators for arousal and negatively valenced states after hearing negative emotional sounds from humans or conspecifics, which indicates that dogs recognised the different valences of the emotional sounds.…”
Section: Discussionmentioning
confidence: 99%